Natural extracts, honey, and propolis as human norovirus inhibitors - Ruoff, Kerstin; Devant, Jessica; Hansman, Grant S. (Scientific reports, 2022)
Norovirus is the most important cause of acute gastroenteritis, yet there are still no antivirals, vaccines, or treatments available. Several studies have shown that norovirus-specific monoclonal antibodies, Nanobodies, and natural extracts might function as inhibitors. Therefore, the objective of this study was to determine the antiviral potential of additional natural extracts, honeys, and propolis samples. Norovirus GII.4 and GII.10 virus-like particles (VLPs) were treated with different natural samples and analyzed for their ability to block VLP binding to histo-blood group antigens (HBGAs), which are important norovirus co-factors. Of the 21 natural samples screened, date syrup and one propolis sample showed promising blocking potential. Dynamic light scattering indicated that VLPs treated with the date syrup and propolis caused particle aggregation, which was confirmed using electron microscopy. Several honey samples also showed weaker HBGA blocking potential. Taken together, our results found that natural samples might function as norovirus inhibitors.
Gesehen am 04.08.2022